(untitled) (Iter, 2022)
The work o f art has been assimilated to mimesis -imitation- in ancient Greece. When a man succeeded in imitating nature. its harmony. order and perfection. it was said that he had created a work o f art. There is. nevertheless, a distance between the thing represented in the work o f art and the work itself There is. in the first place, a meaning o f the work. which goes beyond the thing that is being represented. beyond the author and his time. In the second place, we find in the work o f art. a relationship between beauty and trnth. By truth. in this case, we understand the unconcealedness. the dis-covering o f what is. And fmally. it musí be taken in consideration the active role played by the person who contemplates the work o f art.